Does quality-adjusted human capital matter for economic growth of Malaysia: Time series analysis - Putri, Amelia; Bellamy, Emily (Asian Journal of Economics and Empirical Research, 2024)
Human capital plays a crucial role in driving productivity development and enhancing the standard of living. Human capital refers to the collective knowledge and skills possessed by individuals, which significantly contribute to enhancing productivity and are closely linked to economic growth and development. The significance of human capital in driving innovation and productivity in the case of Malaysia cannot be overlooked. The primary objective of this study is to conduct an empirical analysis of the impact of human capital on the economic growth (EG) of Malaysia over the period from 1990 to 2022. This study utilized quality-adjusted human capital to accurately reflect the underlying significance of human capital. Hence, this study contributes to the existing body of literature by using quality-adjusted human capital in the case of Malaysia. To check the cointegration among variables, this study uses the Fisher Type Bayer-Hanck cointegration test and Johansen cointegration techniques. Using the ARDL approach, we find a positive impact of human capital on economic growth. This implies that labor with developed human capital is more productive and hence contributes more to economic growth. To optimize the positive impact of human capital on economic growth in Malaysia, it is imperative to establish a comprehensive array of policy recommendations that encompass both the quantity and quality of human capital development.